The Urgency of Quality Human Resources Towards Sharia Banking Efficiensy - Yeni Suryani; Indar Fauziah Ulfah (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
Sharia Banks as banks that carry out their business activities based on sharia principles, have an important role in financial institutions in Indonesia. This research analyzes how important quality human resources are in ensuring sharia banks can operate efficiently and sustainably. The research method used is qualitative analysis with a literature study or literature review approach. This research shows that the development of quality human resources is very necessary in achieving efficiency in Sharia Banking activities. Quality SDI must have sharia-based human resource competencies. And also as a Muslim who works in sharia banking, you must obey Allah. Increasing SDI competency can be done internally and externally. Human Resources’ competencies, characteristics, conformity with Islamic principles are very influential in determining how Islamic banking can work and develop. In this way, sharia banks can improve service quality, increase credibility, and increase customer satisfaction so as to achieve an efficient sharia bank